Epidemiology, diagnosis, preoperative evaluation and prognostic assessment of upper-tract urothelial carcinoma (UTUC) - Soria, Francesco; Shariat, Shahrokh F; Lerner, Seth P; Fritsche, Hans-Martin; Rink, Michael; Kassouf, Wassim; Spiess, Philippe E; Lotan, Yair; Ye, Dingwei; Fernández, Mario I; Kikuchi, Eiji; Chade, Daher C; et al. (World journal of urology, 2017)
PURPOSE: Upper-tract urothelial carcinoma (UTUC) is a relatively uncommon disease with limited available evidence on specific topics. The purpose of this article was to review the previous literature to summarize the current knowledge about UTUC epidemiology, diagnosis, preoperative evaluation and prognostic assessment. METHODS: Using MEDLINE, a non-systematic review was performed including articles between January 2000 and February 2016. English language original articles, reviews and editorials were selected based on their clinical relevance. RESULTS: UTUC accounts for 5-10 % of all urothelial cancers, with an increasing incidence. UTUC and bladder cancer share some common risk factors, even if they are two different entities regarding practical, biological and clinical characteristics. Aristolochic acid plays an important role in UTUC pathogenesis in certain regions. It is further estimated that approximately 10 % of UTUC are part of the hereditary non-polyposis colorectal cancer spectrum disease. UTUC diagnosis remains mainly based on imaging and endoscopy, but development of new technologies is rapidly changing the diagnosis algorithm. To help the decision-making process regarding surgical treatment, extent of lymphadenectomy and selection of neoadjuvant systemic therapies, predictive tools based on preoperative patient and tumor characteristics have been developed. CONCLUSIONS: Awareness regarding epidemiology, diagnosis, preoperative evaluation and prognostic assessment changes is essential to correctly diagnose and manage UTUC patients, thereby potentially improving their outcomes.
Keywords: nádory ledvin; neoadjuvantní terapie; Humans; karcinom z přechodných buněk; New technologies; UTUC; ureteroskopie; rizikové faktory; Kidney Pelvis; Aristolochic Acids; lidé; Epidemiology; dědičné nepolypózní kolorektální nádory; Lymph Node Excision; Risk factor; ledvinná pánvička; Colorectal Neoplasms, Hereditary Nonpolyposis; Ureteroscopy; Ureteral Neoplasms; nádory močového měchýře; prognóza; Carcinoma, Transitional Cell; Neoadjuvant Therapy; předoperační péče; Predictive tools; kyseliny aristolochové; lymfadenektomie; nádory močovodu; Preoperative Care; Urinary Bladder Neoplasms; Kidney Neoplasms; Prognosis; Diagnosis; Risk Factors